Detection of Brucella melitensis in milk and serum samples of goats by serological and molecular techniques - LONKAR, SWAPNIL; THORAT, VARSHA; GANDGE, RAJASHREE; PHARANDE, RAJESH; GAIKWAD, SANDEEP (The Indian Journal of Animal Sciences, 2023)
The present investigation was planned for the detection of brucellosis in goats using serological and molecular techniques. A total of 500 clinical samples (250 milk and 250 serum) of goats were collected. All the milk samples were screened by Milk Ring Test and Enzyme-Linked Immunosorbent Assay and serum samples with i-ELISA. Further, the positive milk and serum samples were subjected to 16SrRNA and OMP-31 PCR assays. Results showed the seropositivity of brucellosis was 34.8% and 16% from milk and serum samples of goats by ELISA, respectively and 2.8% by MRT. The results of 16SrRNA PCR detected B. abortusS19, in 32 (36.78%) milk samples and 10 (25%) serum samples by showing an amplicon of 1412 bp. Similarly, the OMP-31 PCR assay tested positive for B. melitensis Rev1, in 22 (25.28%) milk and 05 (12.5%) serum samples by showing an amplicon of 720 bp. Hence, this study is helpful for the detection of brucellosis in goats by using milk and serum samples. The study has generated evidence on the distribution of Brucella melitensis in milk and demonstrated the need to aware people about the importance of boiling milk before consumption in household and thus reduce the risk of infection in human beings.